The The Effect Of Debt Covenant, Financial Distress to Accounting Conservatism, Accounting: The Effect Of Debt Covenant, Financial Distress to Accounting Conservatism, Accounting - Siska, Arita Siska Febrianti (Jurnal Akuntansi UMMI, 2022)
This research aims to examine the effect of debt covenant, financial distressto accounting conservatism to manufacture companies that listed in the Indonesia Stock Exchange. The sample selection by purposive sampling method and 47 companies qualified as sample or 141 observations. This hypothesis testing in this research used multiple linier regression model. Partially, the result indicates that debt covenant, financial distress has effect to accounting conservatism.